The effect of gamma irradiation on chitosan and its application as a plant growth promoter in Chinese kale (Brassica alboglabra) - Mohd Hafez Mohd Isa; Yasir M.S.; Hasan A.B.; Fadilah N.I.M.; Hassan A.R. (American Institute of Physics Inc., 2024)
Indexed by WOS/Scopus